Permainan kartu edukatif, kreativitas, dan pemahaman konsep dalam pembelajaran Biologi - Nisa Nur Azizah; Hayat Sholihin; Lilit Rusyati; Fitri Kania (Curricula: Journal of Curriculum Development, 2026)
Science learning in junior high schools tends to emphasize memorization over the development of higher-order competencies, and non-digital learning approaches are rarely used. This study aimed to determine the effectiveness of an educational card game in enhancing students' creativity and understanding of Biology. A convergent, quasi-experimental, mixed-methods study was conducted with 31 eighth-grade students in Bandung. The study was conducted over four weeks, with the experimental group designing a card game about the excretory system, while the control group created a conventional poster. Creativity was measured using the CPAM, and conceptual understanding was measured using a multiple-choice test. The results showed that the experimental group had higher creativity across all CPAM dimensions and demonstrated a significant increase in understanding with a moderate N-gain compared to the control group, which only achieved a low category. A strong correlation between creative engagement and conceptual growth suggests a mutually reinforcing relationship. Five qualitative mechanisms were identified: iterative design deepens understanding, peer playtesting provides formative feedback, creative constraints encourage problem-solving, collaborative knowledge construction, and kinesthetic learning through card manipulation. These findings confirm that creating card games is a practical, low-cost strategy for Biology classrooms with limited resources.